Diffusion‐Controlled Z‐Scheme‐Steered Charge Separation across PDI/BiOI Heterointerface for Ultraviolet, Visible, and Infrared Light‐Driven Photocatalysis. (26th June 2021) - Ben, Haijie; Liu, Yong; Liu, Xiao; Liu, Xiufan; Ling, Cancan; Liang, Chuan; Zhang, Lizhi
Abstract: Constructing heterojunctions is an efficient approach for enhancing charge separation to optimize photoreactivity. Although the aligned built‐in electric fields across the heterointerface are generally considered as the main driving force for charge separation, diffusion‐controlled charge separation also happens, which is poorly investigated in photocatalytic heterojunctions. Here, a perylene‐3, 4, 9, 10‐tetracarboxylic diimide (PDI)–bismuth oxyiodide (BiOI) heterojunction is elaborately fabricated by in situ successive ion layer adsorption and reaction (SILAR) methods. Utilizing Kelvin probe force microscopy (KPFM), the local separation of photogenerated charge carriers across the heterointerface is directly mapped, which obeys a Z‐scheme mechanism. Experimental results and theoretical simulations reveal that the differences of electron densities between PDI and BiOI enable a diffusion‐controlled charge separation process, which overwhelm that of built‐in electric fields across heterointerfaces. Benefiting from the effective charge separation driven by a diffusion‐controlled driving force, this PDI/BiOI heterojunction exhibits superior photocatalytic activities even under infrared (IR)‐light irradiation. These findings highlight the importance of diffusion‐controlled charge separation, and also offer useful roadmaps for the design of high‐performance heterojunction photocatalysts for down‐to‐earth applications. Abstract : Swimming upstream driven by the transient diffusion electric field, the photoinduced electrons of perylene‐3, 4, 9, 10‐tetracarboxylic diimide (PDI) swim toward bismuth oxyiodide (BiOI) across the PDI/BiOI heterointerfaces under illumination, overcoming the aligned built‐in electric field.